La gamificación y el aprendizaje de la geometría, en el séptimo grado, de la escuela de Educación Básica Zoila Alvarado de Jaramillo” período 2021-2022 - Córdova Suing, Erika Lisbeth (2022)
This research deals with: "Gamification and learning of geometry, in the seventh grade, of "Zoila Alvarado de Jaramillo" basic education school lective year 2021-2022"; for which the following general objective was proposed: Establish the relationship of gamification as a geometry learning strategy, which allowed to investigate the methodological strategies that can be used to implement gamification in the classroom; likewise, it worked with the different methods that helped to base the investigation and based on the same infer criteria on the raised topic, the population was constituted by 34 students and a teacher, which allowed to solidify the problem in a bank of questions. Before which it was determined that the research reveals the different gamification techniques to put them into practice during the development of a class. For which it is concluded that the use of gamification is necessary to strengthen the learning of geometry in seventh grade students, thus helping them to develop better and facilitating their understanding of the mentioned topic. Keywords: gamification, meaningful learning, geometry, strategies of learning